Is Moore’s Moral Objectivist Argument Sufficient Against Moral Relativism? - Burhan Başarslan (Marifetname)

(untitled)
This study aims to expose certain weaknesses in Moore’s moral objectivist argument against moral relativism and subjectivism. It suggests that a moral objectivist argument has to explain moral diversity against moral relativism. Moral relativism is one of the most critical debates in metaethics, and it can be interpreted in two different ways: one as moral realism and the other as moral anti-realism. Moral realism, when reduced to moral objectivism, excludes moral relativism and subjectivism beyond moral realism. I will refer to this interpretation as narrowed moral realism. But moral realism can be extended in an inclusive way such as moral subjectivism and relativism. I will refer to this as extended moral realism. Due to the focus of the study, I will introduce both extended moral realism and narrowed moral realism in the introduction section. Then, I will address G. E. Moore's narrowed moral realism. I will criticize his arguments for their failure to explain the diversity of moral codes. Finally, I suggest that moral subjectivism and moral relativism can be appropriately addressed within extended moral realism. Contrary to Moore's claims, I contend that moral relativism and moral subjectivism would be claims within moral realism. I also evaluate the two main claims from a moral realist perspective. Moral subjectivism claims that moral reality is constructed by an individual’s mental state. Moral relativism argues that social codes of human conduct completely determine moral reality. In the first section of the study, I discussed moral relativism from a Moorean perspective, which asserts that there are self-evident and indefinable truths at the foundation of objective morality. The second section contends that if Moore is correct, however, it necessitates an explanation for why different cultures accept different moral codes. The third section argues the fact that Moore fails to provide any explanation for this. In the conclusion part, I claim that moral relativism and moral subjectivism can be viewed as moral realist theories based on the failure of Moore's arguments.